E-learning challenges and opportunities for students with special needs during COVID-19 Pandemic - Talafha, Abdulhameed (Technium Social Sciences Journal, 2022)
This empirical study aims to discuss the impact of the COVID-19 pandemic on the learning process of the students with special needs. In this context, the study focuses on addressing the challenges and opportunities that should be taken into account by teachers, especially after the emergence of ‘e-learning’ (also known as ‘distance education’ and/or ‘remote learning’) era. The study further intends to identify accessibility barriers and challenges to learning for students with special needs in the context of remote learning. It also aims to recommend a framework that, in addition to specifying the challenges, suggest several systematic responses and recovery for these challenges for the special education sector’s consideration. The study concluded that COVID-19 pandemic has made a substantial impact on the education sector. In fact, the pandemic has changed the way in which education is delivered. Students, parent or guardians, and teachers had to change the way they access, support or deliver education. The pandemic highlighted gaps in digital skills, adaptation of technology to teaching and learning.